Perancangan Aplikasi Surat Perintah Perjalanan Dinas Berbasis Web pada Biro Administrasi Pembangunan Provinsi Sumatera Utara - Syah Zanul Husna; Winda Cahyanti; Yusuf Ramadhan Nasution (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to process and manage official travel orders (SPPD) from the Web-based Office Travel Order Application System Design at the Bureau of Development Administration of North Sumatra Province based on the Web. In this design, the data used is a Service Travel Order where data collection is by observation, interview, and literature study. After collecting data, it was found that the recording of SPPD was still manual, namely using bookkeeping media. So from these problems, researchers made a Web-based Office Travel Order Application Design using PHP and MySQL programming made with the Sublime Text editor and Bootstrap. The results of this application design are inputting SPPD, inputting employee data, searching SPPD, and making SPPD. Keywords: SPPD, PHP, MySQL, Website